2016
DOI: 10.1097/bth.0000000000000118
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of Fixation of a Distal Radius Fracture With a Volar Locking Plate Through a 10 mm Approach

Abstract: The management of distal radius fractures has dramatically improved due to the development of a locking plate system. In addition, mini-invasive surgery has been performed in a lot of surgical fields in recent years. The aim of the present study is to investigate the possibility of fixation of a distal radius fracture with a volar locking plate through a 10 mm approach. Eighteen patients with distal radius fracture (mean age: 66 y; range, 28 to 88 y; 8 males and 10 females) were operated on using a volar locki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 21 publications
1
23
0
1
Order By: Relevance
“…For volar displaced fractures, good functional outcomes can be obtained using DVLP in our study. These outcomes were comparable to our previous study about dorsal displaced fractures 14 (►Table 2). It was suggested that surgical treatment using DVLP is useful to treat DRF with marginal rim fragments.…”
Section: Videosupporting
confidence: 90%
“…For volar displaced fractures, good functional outcomes can be obtained using DVLP in our study. These outcomes were comparable to our previous study about dorsal displaced fractures 14 (►Table 2). It was suggested that surgical treatment using DVLP is useful to treat DRF with marginal rim fragments.…”
Section: Videosupporting
confidence: 90%
“…A recent study by Naito et al explored the possibility of distal radius fixations with a mere 10-mm incision for a volar locking plate. (12) Most surgeons are more familiar with the traditional longitudinal approach, and our results showed that patients were not averse to such incisions. However, perceptions of scar aesthetics vary with individual choice and show marked interpersonal variability, as seen from our survey of first impressions of volar wrist scars.…”
Section: Discussionmentioning
confidence: 62%
“…13 The most common complications of this treatment are extensor tendon or flexor tendon injury, flexor pollicis rupture, complex regional pain syndrome, and loss of reduction. 3 Hardware failure is a relatively rare occurrence.…”
Section: Discussionmentioning
confidence: 99%